Pemanfaatan Sistem Pendukung Keputusan Pemberian Kredit Di Perum Pegadaian - Wijaya, Danang; , Gunawan Ariyanto, Ph.D (2015)
Technique decision making used in analysis wisdom in pawnshop is ahp (analytic hierarchy process). AHP used in in pawnshop which is to determine a candidate debtors which eligible to receive credit considering criterias set by the pawnshop. Purpose in the research also there are three, ( 1 ) want to know the procedure the use of the support system decree ( spk ) the provision of credit in pawnshop.( 2 ) want to know of factors affect pawnshops use the support system decree ( spk ). Place research to writing thesis is located at a branch office pawnshop surakarta.Primary data in this research that is data input customers / the applicant and the process spk the provision of credit criteria. Data Secondary that is reading materials books ddan journal research.Data collection use observation, the literature study, and interview.Technique analysis data using descriptive. Conclusion in this study ( 1 ) the support system this decision can produce alternative the decision to give credit for pawnshops.The support system this decision can run wisdom decision credit he has set by manager.In spk this is facilities to set criteria belong sub criteria and sub-sub the criteria.The support system this decision can produce report proposal decision entreaty credit.( 2 ) the system the support system decision in a ahp in pawnshop in general Influenced the saving of time, increase the effectiveness of managerial, and increase productivity analysis.Specifically influenced by a factor of: factors Technology,, factors management company, factors personal the staffs, factors usefulness and factors benefits